2009
DOI: 10.1530/rep-08-0035
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of two-pore domain K+ channels in bovine germ cells

Abstract: Two-pore domain K C (K 2P ) channels that help set the resting membrane potential of excitable and nonexcitable cells are expressed in many kinds of cells and tissues. However, the expression of K 2P channels has not yet been reported in bovine germ cells. In this study, we demonstrate for the first time that K 2P channels are expressed in the reproductive organs and germ cells of Korean cattle. RT-PCR data showed that members of the K 2P channel family, specifically KCNK3, KCNK9, KCNK2, KCNK10, and KCNK4, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The expression of the K 2P channel member transcripts identified by RT-PCR was subsequently studied at the protein level. The specificity and sensitivity of the antibodies used in these experiments were confirmed in previous studies (Kang et al 2007, Hur et al 2009). Each antibody was specific for its own antigen (Supplementary Figure 1, see section on supplementary data given at the end of this article).…”
Section: Molecular Characterization Of Ksupporting
confidence: 83%
See 1 more Smart Citation
“…The expression of the K 2P channel member transcripts identified by RT-PCR was subsequently studied at the protein level. The specificity and sensitivity of the antibodies used in these experiments were confirmed in previous studies (Kang et al 2007, Hur et al 2009). Each antibody was specific for its own antigen (Supplementary Figure 1, see section on supplementary data given at the end of this article).…”
Section: Molecular Characterization Of Ksupporting
confidence: 83%
“…Recent studies have found that K 2P channels are expressed in the mammalian reproductive organ and cells, such as in human cytotrophoblast cells, placental villous tissue and trophoblast cells, myometrium, the placental vascular system, and uterine smooth muscle cells (Bai et al 2005a, 2005b, Tichenor et al 2005, Wareing et al 2006, Chow et al 2007. In addition, a previous study from our laboratory also found these channels to be expressed in bovine ovaries, testis, and germ cells (Hur et al 2009). Furthermore, they were also present in monkeys, where their expression was restricted to sperm (Chow et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“…For instance, a study by Ferrer et al [67] found that MMP2 co-localizes with acrosin on the inner acrosomal membrane of bull spermatozoa, where the authors suggest the protease may mediate sperm penetration at the zona pellucida as matrix metalloproteases function to cleave extracellular matrix components. Another DMR was identified in the KCK4 gene, a member a two-pore domain potassium (K 2P ) channel family [68], where potassium channels have important physiological roles in the acrosome reaction and fertilization [69]. In bull spermatozoa, a study by Hur et al [68] reported that the protein of KCK4 localizes to the equatorial region of acrosome reacted sperm, and that inhibitor of the K 2P channels reduces not only fertilization but also development of bovine and mouse embryos in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The specific function of transmembrane protein TMEM110 is unknown. Among two additional candidate genes RBFOX1 and KCNK10, the latter one is expressed in germ lines and can have indirect link with semen quantity (Hur et al, 2009).…”
Section: Discussionmentioning
confidence: 99%